2012
DOI: 10.1007/s00595-012-0246-1
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between two types of limited sympathetic surgery for palmar hyperhidrosis

Abstract: PurposeEndoscopic thoracic sympathetic surgery is effective for treating palmar hyperhidrosis, although compensatory sweating (CS) is a significant and annoying side effect. The purpose of this study was to compare the results of limited resection at two different locations.MethodsFrom May 2004 to June 2009, T3 sympathicotomy (group I) was performed in 46 patients and T3,4 ramicotomy (group II) was performed in 43 patients during the same period. T3 sympathicotomy (group I) and T3,4 ramicotomy (group II) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…In this regard, Gossot et al [15], in a two-braced retrospective study evaluating classical sympathectomy (54 patients) and Wittmoser's approach (62 patients), reported a significant risk of recurrence in selective resection group (0 vs 5; p < 0.05), though no difference in postoperative compensatory sweating was found (72.2% vs 70.9%). On the other hand, Hwang et al [16], comparing 46 patients undergoing sympathicotomy and 43 undergoing ramicotomy, found slight significant differences in satisfaction rate (91.3% vs 79.1%, p = 0.067) and dryness (82.6% vs 25.6%; p < 0.001). Moreover, the incidence of persistent hand sweating and CH was higher in the selective group than ).…”
Section: Discussionmentioning
confidence: 97%
“…In this regard, Gossot et al [15], in a two-braced retrospective study evaluating classical sympathectomy (54 patients) and Wittmoser's approach (62 patients), reported a significant risk of recurrence in selective resection group (0 vs 5; p < 0.05), though no difference in postoperative compensatory sweating was found (72.2% vs 70.9%). On the other hand, Hwang et al [16], comparing 46 patients undergoing sympathicotomy and 43 undergoing ramicotomy, found slight significant differences in satisfaction rate (91.3% vs 79.1%, p = 0.067) and dryness (82.6% vs 25.6%; p < 0.001). Moreover, the incidence of persistent hand sweating and CH was higher in the selective group than ).…”
Section: Discussionmentioning
confidence: 97%
“…In these cases, it is crucial to emphasize and clarify to patients before the first operation that this reversibility is a hypothetical advantage, which may not become real even after the clips removal (33). The chosen method to perform the trunk interruption will ultimately depend on the available instruments and the surgeon's preference, since many studies (34)(35)(36) suggest that the results among all the described techniques are comparable regarding symptoms resolution, recurrence rates and incidence of CH.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Moreover, Hwang et al found that, compared to T3 sympathicotomy, the unexpected lower extremity sweating that occurred after T3, 4 ramicotomy resulted in lower satisfaction levels, and there were no significant differences between the two groups in age and gender distribution. While ramicotomy was considered an efficient procedure for the treatment of palmar hyperhidrosis and had the potential benefit of enabling greater anatomical resection; it took longer operating time and contributed to more severe compensatory sweating (17). In the present study, we conducted 24 sympathectomies on 12 patients with primary palmar hyperhidrosis who underwent thoracoscopic bilateral selective sympathectomy (ramicotomy) and there was no significant difference between age, gender, weight, BMI, and compensatory sweating.…”
Section: Discussionmentioning
confidence: 78%